Cultural Analyses of the Olonkho Epic Text by P. A. Oyunsky “Nyurgun Bootur the Swift” - Popova, Galina Semenovna (Journal of History Culture and Art Research, 2018)
This olonkho, made by the founder of the Yakut literature, the first Sakha linguist, Platon Oyunsky, is first time undergoing through a vast specific cultural analyses due to the 125th anniversary of its author. As known, this work is said to be a literature olonkho, but it can claim the role of a canonic text of an olonkho. Unlike the classical olonkho, the author enriched this epic text by one significant character, named Taas kiele ogo, who, in our understanding, reveals the core thought of the Sakha people about the taboo to violate the cosmic balance among the three worlds, the Upper, Middle and Lower. Hereof we come to the highlighted normative function of the text and that is the rational outcome of our research. In general, the semantic range contains value and cognitive aspects. The other methods of interpretation also reveal the newly found aspects in the text of this olonkho, which is like representative one for the Sakha culture. This is the result of hermeneutic analysis. Other methods of reading used in the study are narrative, semiotic, symbolic, and information analysis. They consistently complement each other and bring the researcher to the understanding of the hidden meaning in the text. Methods of ethnomethodology, ethological research, the study of communicative intention, functional and structural analysis reveal ethno-cultural social features. They also show the degree of stability of the system under study. All the methods used reveal previously identified aspects in the text. The olonkho is a hallmark of the Sakha culture. The perspectives of the detailed work in future make us feel sure of the theoretical and practical significance of the gained results, which are based on cultural scientific methodology. Non-classical approach of scientific methodology is used by the author. According to this approach, the parts are integrated and the text of the culture is an indivisible whole. The text contains a linguistic entity and the coded address information.